2017
DOI: 10.1080/10410236.2017.1333561
|View full text |Cite
|
Sign up to set email alerts
|

It’s Your Place: Development and Evaluation of an Evidence-Based Bystander Intervention Campaign

Abstract: Preventing sexual assault on college campuses is a national priority. Bystander intervention offers a promising approach to change social norms and prevent sexual misconduct. This study presents the implementation and evaluation of a theory-based campaign to promote active bystander intervention. The theory of planned behavior (TPB) served as a conceptual framework throughout campaign development and evaluation. Formative research published elsewhere was used to develop campaign strategies, communication chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…that exposure to this had a significant effect on self-efficacy and controllability of bystanders towards the intention to intervene to prevent a sexual assault from happening. After seeing the campaign, participants of the study reported that they had a more positive attitude towards bystander intervention, a greater sense that the important people around them would expect them to intervene, and that they were equipped with more knowledge and skills to prevent a sexual assault occurrence (Sundstrom et al, 2018 , 2020). This implies that the media campaign successfully encouraged students to have better self-efficacy and controllability in their academic life.…”
Section: Subjective Norms Media and Adherence To Quarantinementioning
confidence: 99%
“…that exposure to this had a significant effect on self-efficacy and controllability of bystanders towards the intention to intervene to prevent a sexual assault from happening. After seeing the campaign, participants of the study reported that they had a more positive attitude towards bystander intervention, a greater sense that the important people around them would expect them to intervene, and that they were equipped with more knowledge and skills to prevent a sexual assault occurrence (Sundstrom et al, 2018 , 2020). This implies that the media campaign successfully encouraged students to have better self-efficacy and controllability in their academic life.…”
Section: Subjective Norms Media and Adherence To Quarantinementioning
confidence: 99%
“…Bystander intervention involves a level of planning (McMahon et al, 2015; Rosval, 2013) but the potentially reactive nature of intervention remains unexplored. Self‐efficacy is also clearly important in explaining intervention (Sjögren et al, 2020; Sundstrom et al, 2018), however, there is a need to differentiate this from other control factors. Furthermore, moderation contributions between social cognitive variables have not been examined in the context of bystander intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐efficacy involves perceived skill and competency over a behaviour (Ajzen, 1991 ). Existing studies tend to replace or conflate perceived behavioural control with self‐efficacy (Banyard, 2008 ; Banyard & Moynihan, 2011 ; Coker et al, 2011 ; McMahon et al, 2015 ; Pöyhönen et al, 2010 ; Rosval, 2013 ; Salmivalli, 2010 ; Sjögren et al, 2020 ; Sundstrom et al, 2018 ). However, these factors are likely to provide independent insight into intervention as factor analytic studies illustrate their independent effects on intentions and behaviour (Armitage & Conner, 1999a , 1999b ; Conner & Armitage, 1998 ; Manstead & van Eekelen, 1998 ; Sparks et al, 1997 ; Terry & O’Leary, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Derived from the Theory of Reasoned Action (TRA; Fishbein & Ajzen, 1975), the Theory of Planned Behavior (TPB; Ajzen, 1991) is widely known for its ability to predict and change health behaviors and has been applied in recent studies to BI programming related to sexual assault (Hoxmeier et al, 2018; Sundstrom et al, 2018). The TPB posits that one's intention (or overall motivation/readiness to perform a behavior) is the principal determinant of behavior, barring any deficiency in skill or environmental constraint.…”
Section: Introductionmentioning
confidence: 99%